PENGARUH GAYA KEPEMIMPINAN DEMOKRATIS, KOMPETENSI DAN KEPUASAN KERJA TERHADAP KINERJA PEGAWAI PADA DINAS BADAN PERENCANAAN PEMBANGUNAN DAERAH (BAPPEDA) PROVINSI BALI - I Gede Arya Lilacita; Agus Wahyudi Salasa Gama; Ni Putu Yeni Astiti (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2022)
Employee performance assessment is a very important thing in an organization to achieve its goals, so that various policies must be carried out by the organization to improve employee performance. Good performance is an outcome that every organization wants to achieve. Improved employee performance can be seen from the democratic leadership style, competence and job satisfaction. This study aims to examine and obtain empirical evidence of the effect of democratic leadership style, competence and job satisfaction on employee performance at the Bali Provincial Planning Development Agency (BAPPEDA). The population in this study were employees of the Regional Planning Development Agency (BAPPEDA) of Bali Province. The research sample was 72 employees who were determined by the census method. The analytical tool used is multiple linear regression analysis. The results of this study indicate that democratic leadership style and competence have a positive effect on employee performance at the Bali Provincial Planning Development Agency (BAPPEDA). While job satisfaction has no effect on employee performance at the Regional Planning Development Agency (BAPPEDA) Bali Province. Further research can develop this research by using other variables that theoretically have an influence on employee performance, such as work ability, work discipline and work experience